GIS for Environmental Decision-Making - Lovett, Andrew (CRC Press, 2009)
Environmental applications have long been a core use of GIS. However, the effectiveness of GIS-based methods depends on the decision-making frameworks and contexts within which they are employed. GIS for Environmental Decision-Making takes an interdisciplinary look at the capacities of GIS to integrate, analyze, and display data on which decisions must be based. It provides a broad prospective on the current state of GIS for environmental decision-making and emphasizes the importance of matters related to data, analysis, and modeling tools, as well as stakeholder participation.